OMNIA-1: A phase I/II study, an IL-2R-βγ targeted antibody-IL-2 fusion protein, as monotherapy or in combination with anti-PD-1 or anti-CTLA-4 antibodies, in patients with advanced melanoma - de Velasco, Guillermo; Eigentler, Thomas; Isambert, Nicolas; Mouton, Julie; Robert, Caroline; Schusterbauer, Claudia Michaela; Vijayakumar, Jayanthi (Journal of clinical oncology, 2023)
TPS9599Background: ANV419 is a potent and selective IL-2Rβγ targeted antibody IL-2 fusion protein, designed to enable the delivery of high dose interleukin-2 (IL-2) to patients in order to stimulate anti-tumour response and minimise toxicities. Recombinant IL-2 (proleukin) induces durable responses in approximately 10% of patients with melanoma. Signalling through IL-2Rα expressing cells is believed to limit its therapeutic potential in cancer. By eliminating binding to IL-2Rα, ANV419 could lead to increased anti-tumor effect while increasing tolerability. The ANV419-001 first-in-human study (NCT 04855929) demonstrated that ANV419 preferentially stimulates cytotoxic CD8+ T and natural killer (NK) cells over immunosuppressive regulatory T cells, with a significantly longer half-life than that of conventional IL-2. The safety and tolerability data from this study confirmed that ANV419 delivers high molar equivalents of IL-2 in a tolerable and convenient way. Methods: ANV419 is being evaluated in a global multicentre, open-label, randomized Phase I/II study in patients with unresectable or metastatic cutaneous melanoma to assess the safety and efficacy of intravenous ANV419 as monotherapy and in combination with anti-PD1 or anti-CTLA-4 antibodies. The OMNIA-1 study leads in with a monotherapy dose expansion part, followed by a combination dose-finding with either anti-PD-1 or anti-CTLA-4 and a combination dose expansion part. ANV419 is administered intravenously every 2 weeks as monotherapy and every 3 weeks when given in combination. Patients with advanced cutaneous melanoma, no active brain metastases and whose disease has progressed on or following at least 1 line of standard of care immunotherapy are eligible. In Part 1, a total of 30 patients will be randomised and evaluated for response to Q2W ANV419 monotherapy (108 µg/kg or 243 µg/kg). In Part 2, escalating doses of Q3W ANV419 are evaluated to define the maximum tolerated dose (MTD) and recommended Phase 2 dose (RP2D) in combination with pembrolizumab (200 mg) or ipilimumab (3 mg/kg). In Part 3, the efficacy and safety of ANV419 in combination with the approved doses pembrolizumab or ipilimumab will be evaluated using a Simon's 2-stage design. Up to 130 patients are planned to be enrolled. Patients will be stratified according to BRAF mutation status. AEs are assessed according to CTCAE V5.0. Tumour response is determined using RECIST 1.1 criteria. The study is conducted at sites in the US, France, Spain, Germany, Italy, and UK. The first patient was dosed in December 2022. Preliminary monotherapy efficacy data are expected by Q1/2024. Clinical trial information: NCT05578872.